Testing and design of stainless steel staggered bolted connections. (15th March 2021) - dos Santos, João de J.; Liang, Yating; Zhao, Ou; de Andrade, Sebastião A.L.; de Lima, Luciano R.O.; Gardner, Leroy; Vellasco, Pedro C.G. da S.
Highlights: The net section failure behaviour and capacity of stainless steel staggered botled connections are studied. Tension tests on 31 stainless steel staggered bolted connections are conducted. The influences of the staggered bolt hole pattern and pitches on the failure loads and modes are disscussed. The accuracy of the codified design rules is assessed, indicating conservatism. A new design approach based on the continuous strength method is proposed and results in substantially improved predictions. Abstract: The present paper reports a thorough experimental investigation into the net section failure behaviour and capacity of stainless steel staggered bolted connections in tension. The testing programme was carried out on 31 stainless steel staggered bolted connection specimens, with 18 made of austenitic stainless steel (grade EN 1.4301), 7 made of duplex stainless steel (grade EN 1.4462) and 6 made of ferritic stainless steel (grade EN 1.4016). The geometric parameters, including the transverse and staggered pitches, and the staggered bolt hole patterns of the connection specimens, were varied. The test setup and procedures, as well as the key experimentally observed results, including the net section failure modes and loads, are reported in detail. The experimentally obtained net section failure loads and modes are analysed and discussed, and then utilised to assess the accuracy of the established design rules for stainless steel staggered bolted connections, given in the European, American and Australian/New Zealand standards. All three examined standards consider (i) net section fracture and (ii) gross section yielding in the design of stainless steel staggered bolted connections, and specify that the design failure load shall be taken as the minimum value calculated from all potential failure modes. It was found that the current design standards lead to overly conservative and scattered failure load predictions as well as inaccurate failure mode predictions. A new design approach based on the continuous strength method (CSM) is proposed, and shown to result in substantially improved predictions of both failure loads and failure modes.